Socio-Economic Impacts of Tourism Development in Rural Area of Sembalun East Lombok West Nusa Tenggara - Vitriani, Ch Dian; Sudibyo, Djoko; Hermantoro, Henky (Institut Pariwisata Trisakti, 2017)
Tourism development brings both positive and negative social, economic and environmental impacts, and so does the development of rural tourism in Sembalun. Tourism is considered to have a great potential to improve people's welfare. The Sustainable Livelihood Framework is an instrument used to analyse the socio-economic impact of tourism development on the livelihood of local communities in Sembalun. This research is a replication of previous research in 2010 in Borobudur. This research compares the results of the impact analysis of heritage tourism in Borobudur with rural tourism in Sembalun on community livelihood based on the Sustainable Livelihood Framework instrument, not based on its different tourism attractions. In Sembalun the agricultural and tourism sectors support each other. The tourism sector has also proven to bring positive socio-economic impacts to local communities, such as promoting Micro, Small and Medium Enterprises (MSMEs) products, increasing training and financial supports, job creation, cultural preservation, and pride and feeling of becoming part of the tourism development in their village. Tourism is also considered to have a positive impact in improving people's welfare. The most commonly complained negative impacts are waste as well as concerns that the local culture will be eroded by foreign culture brought by tourists. Keywords: tourism impact, sustainable livelihood framework, sustainable tourism, community based tourism, rural tourism